Movement control in springboard diving - Rewt, D. (University of Edinburgh, 1993)
The challenges of bringing together the theoretical and practical dimensions of a specific sporting skill are complex, and demand an understanding of the different levels of the physical basis of movement. At the biomechanical level, movement is understood in relation to the forces generated by muscles and their interaction throughout the human body. At the neurophysiological level motor behaviour is studied in relation to the neural structures and their functional interactions. At the observational level, the connection between the athlete's movement action and the environment is fundamental to the development of skill. Ultimately, the processes which underlie these relationships are critical to fully comprehend the complex system of human motor performance. This thesis adopts an ecological perspective on movement control, wherein the organism is conceptualised as an open system which acts in relation with its environment. It is appropriate that the explication of this viewpoint is considered in the context of sporting excellence, where the practical application of a variety of movement control theories is particularly germane. In adopting this position, it is recognised that there are competing hypotheses about the nature of movement control.